Morus alba Leaf Lectin (MLL) Sensitizes MCF-7 Cells to Anoikis by Inhibiting Fibronectin Mediated Integrin-FAK Signaling through Ras and Activation of P38 MAPK - Saranya, Jayaram; Shilpa, Ganesan; Raghu, Kozhiparambil G.; Priya, Sulochana (Frontiers in Pharmacology, 2017)
Lectins are a unique class of carbohydrate binding proteins/glycoproteins, and many of them possess anticancer properties. They can induce cell cycle arrest and apoptosis, inhibit protein synthesis, telomerase activity, and angiogenesis in cancer cells. In the present study, we have demonstrated the effect of Morus alba leaf lectin (MLL) on anoikis induction in MCF-7 cells. Anoikis induction in cancer cells has a significant role in preventing early stage metastasis. MLL treatment in monolayers of MCF-7 cells caused significant detachment of cells in a time and concentration dependent manner. The detached cells failed to re-adhere and grew even to culture plates coated with different matrix proteins. DNA fragmentation, membrane integrity studies, annexin V staining, caspase 9 activation and upregulation of Bax/Bad confirmed that the detached cells underwent apoptosis. Upregulation of matrix metalloproteinase 9 (MMP-9) caused a decrease in fibronectin production which facilitated the cells to detach by blocking the fibronectin mediated downstream signaling. On treatment with MLL, we have observed downregulation of integrin expression, decreased phosphorylation of focal adhesion kinase (FAK), loss in FAK-integrin interaction and active ras. MLL treatment downregulated the levels of phosphorylated Akt and PI3K. Also, we have studied the effect of MLL on two stress activated protein kinases p38 MAPK and JNK. p38 MAPK activation was found to be elevated, but there was no change in the level of JNK. Thus our study substantiated the possible antimetastatic effect of MLL by inducing anoikis in MCF-7 cells by activation of caspase 9 and proapoptotic Bax/Bad by blockage of fibronectin mediated integrin/FAK signaling and partly by activation of p38 MAPK.